2016
DOI: 10.1371/journal.pone.0151345
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA-26a in Plasma and Its Potential Diagnostic Value in Gastric Cancer

Abstract: BackgroundIn the past decades, a good deal of studies has provided the possibility of the circulating microRNAs (miRNAs) as noninvasive biomarkers for cancer diagnosis. The aim of our study was to detect the levels of circulating miRNAs in tissues and plasmas of gastric cancer (GC) patients and evaluate their diagnostic value.MethodsTissue samples were collected from 85 GC patients. Plasma samples were collected from 285 GC patients and 285 matched controls. Differentially expressed miRNAs were filtered with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…. Prior studies have noted the importance of detecting circulating miRNAs in the plasma of gastric cancer , oesophageal squamous cell carcinoma , hepatocellular carcinoma and lung cancer . Nevertheless, little is known about circulating lncRNAs in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…. Prior studies have noted the importance of detecting circulating miRNAs in the plasma of gastric cancer , oesophageal squamous cell carcinoma , hepatocellular carcinoma and lung cancer . Nevertheless, little is known about circulating lncRNAs in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…22 miR-148a can suppress tumor proliferation, invasion and metastasis in gastric cancer by regulating several target genes and pathways. 30 In a large profile study of GC, miR-125b was one of the three most important miRNAs involved in the progression-related signature. 26 miR-126, miR-125b and miR-26a were involved in the pathogenesis of many cancers by different mechanisms, acting as oncogenes or tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 In GC, miR-26a suppressed GC growth and metastasis by targeting FGF9, 29 and circulating miR-26a in plasma was a potential marker for diagnosis in GC. 30 In a large profile study of GC, miR-125b was one of the three most important miRNAs involved in the progression-related signature. 31 In the field of functional research, there have been controversies about miR-126 32,33 and miR-125b [34][35][36] in GC, suggesting that they might be expressed in a tissue-specific pattern and have cell content-dependent functions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that exosomal miRNAs can be detected in a variety of body fluids, from blood to breast milk, and that their levels are correlated with patient status [4,5,[60][61][62][63][64][65][66][67][68][69][70][71][72][73] (Table 1). On January 21, 2016, cancer diagnosis using exosomes from blood became commercially available in the US (http://www.exosomedx.com) [6].…”
Section: Diagnosismentioning
confidence: 99%